(untitled) (Global Journal of Science Frontier Research, 2021)
The aim of this study is to determine the length -weight relationship and feeding habits of Oreochromis niloticus in Wudil river Kano state Nigeria. The Length-Weight relationship and feeding habit of Oreochromis niloticus in Wudil river was investigated using One hundred (100) specimens of Oreochromis niloticus. Samples were obtained from the catch of fishermen at landing sites for three months. Fish specimens randomly were easily identified by the dark bands/r stripes found on their tail. Samples were chilled in iced blocks at the point of collection before being transported in a plastic container to the laboratory for further analysis. Total lengths and weights were measured using standard method. The guts were The result of length -weight regression analysis of Oreochmis niloticus is shown in figure I for male, figure II for female II, and combine figure III 12.87, 15.29 and combine sexes 13.72 respectively all indicated allometric growth. The length -weight relationship of male figure I, female figure II and combine sexes figure III showed linear relationship with the significance coefficient of 0.887, 0.939 and 0.904 respectively at 0.05 per cent between length and weight.